Genome sequence of the thermophilic cyanobacterium Thermosynechococcus sp. strain NK55a - Stolyar, Sergey (2019)
The genome of the unicellular cyanobacterium Thermosynechococcus sp. strain NK55a, isolated from the Nakabusa hot spring, Nagano Prefecture, Japan, comprises a single, circular, 2.5-Mb chromosome. The genome is predicted to contain 2,358 protein-encoding genes, including genes for all typical cyanobacterial photosynthetic and metabolic functions. No genes encoding hydrogenases or nitrogenase were identified.